Effect of seed treatment methods on the dynamics of the morphometric characteristics of the Echinacea pallida leaf in ontogenesis - Григоришин, Є. В. (Scientific Progress & Innovations, 2017)
The article investigated the influence on the environmentally safe stimulants dynamics morphometric characteristics of the Echinacea pallida leaf in ontogenesis. It was found that the length of the growing season, a year and a method for pre-treating the seeds was significantly determine the size of the leaves of Echinacea in ontogenesis in terms of width and length. The greatest effect is set to UHF radiation. Other types of treatment efficacy differ little from each other, but not statistically significantly different from control. Increased leaf size in terms of width and length is described by the logarithmic dependence. The most intensive growth processes in the early stages of ontogenesis were occurred in 2012, and the least intensive – in 2015. During the growing season the maximum rate of leaf size growth was characteristic of 2015 and in 2012 this figure was the lowest. Seed pre-treatment influences the dynamics of change in leaf size. A positive stimulatory effect on the growth rate at the beginning of the growing season has «Nanomix» but exhibits the greatest effect of UHF radiation seeds. Between the length and width of the leaf there is a strong positive correlation was statistically significant (r = 0.83, p = 0.00). The correlation between such morphometric characteristics of the leaf, the length and the width may vary over the years. Investigated seed pre-treatment methods does not affect the correlation between the length and width of the leaves.